KASUS DISTOKIA PADA SAPI POTONG DI KECAMATAN KUNIR KABUPATEN LUMAJANG TAHUN 2015 DAN 2016 - Febrianila, Rosiana; Paramita L., Widya; Imam R., Tjuk; Mustofa, Imam; Safitri, Erma; Hermadi, Herry Agoes (Universitas Airlangga, 2018)
Dystocia defined as difficulty of birth. Catlle that experienced dystocia characterized by extended processing time of birth, difficult, and impossible to do without help of human stem. This study aimed to determine the number of and causative factor of dystocia in beef cattle in Kecamatan Kunir Kabupaten Lumajang. Data acquisition used primary data and secondary data. Primary data was obtained from direct observations about management of maintenance, then interviewed the farmers in Kecamatan Kunir. Secondary data was data obtained from the recording belongs to animal health technical officer. The results showed that the prevalence of dystocia in Kecamatan Kunir Kabupaten Lumajang as many as 63 cases or 11,6 % of 543 birth. The result of the research is analyzed using chi square (Ï‡2) method on SPSS 20.0 program and risk factors that increase the incident of dystocia were IB semen which greater than the catlle site, the position of the foetus and inertis uteri can resulting in weakness of the catlle at the age of older and more likely to give birth.